THE RELATIONSHIP BETWEEN SPINOPELVIC PARAMETERS ON RADIOGRAPHY AND THE DEGREE OF LUMBOSACRAL INTERVERTEBRAL DISC HERNIATION ON MRI - Nasrizarni, Nasrizarni; Darinafitri, Irma; Azmy, Abdullah (LPPM Universitas Jambi, 2025)
Given the limited availability of lumbosacral MRI, currently the most accurate modality for assessing the severity of intervertebral disc herniation, in many hospitals in Indonesia, evaluation of spinopelvic parameters on lumbosacral radiographs is expected to serve as an alternative predictor of lumbar disc herniation grade. This study aims to analyze the relationship between spinopelvic parameters and the degree of lumbosacral intervertebral disc herniation, and to identify which parameters are most accurate in predicting the degree of the herniation in patients with low back pain. This research is a retrospective analytic observational study with a cross-sectional design that included 52 patients with low back pain who underwent lumbosacral radiography and MRI at Saiful Anwar General Hospital in 2022–2023. The degree of disc herniation was assessed on sagittal and axial lumbosacral MRI. In contrast, spinopelvic parameters, including pelvic incidence (PI), sacral slope (SS), pelvic tilt (PT), lumbar lordosis (LL), lumbosacral angle (LSA), sacral table angle (STA), and sacral kyphosis (SK), were measured on lumbosacral radiographs. Statistical tests were conducted on four groups (normal, bulging, protrusion, and extrusion). Using Spearman’s test, a correlation was found between lumbar lordosis angle and the degree of lumbosacral intervertebral disc herniation, with p=0.011 (p<0.05). One-way ANOVA showed a significant difference in lumbar lordosis across herniation grades, with p=0.028 (p<0.05). A smaller lumbar lordosis angle was associated with a higher risk of lumbosacral intervertebral disc herniation. Therefore, lumbar lordosis, as one of the spinopelvic parameters, may be considered a predictive factor for lumbosacral disc herniation.